Facile, fine post-tuning of the longitudinal absorption wavelengths of pre-synthesized gold nanorods by introducing sulfide additives1. Issue 65 (16th July 2015) - Park, Youngjin; Kim, Jaeyun
<x xml:space="preserve">Abstract</x> The longitudinal absorption wavelength of pre-synthesized gold nanorods is precisely tuned by introducing controlled amounts of sulfide additives, which allows a powerful second chance to adjust the absorption wavelength of gold nanorods.